Application Anti Microbial Activity Test and Direct Inoculation of Urinary Specimen Test to Increase the Quality of Results and Decrease the Production Cost in Clinical Microbiology Laboratory, Sanglah General Hospital Hospital, Bali-Indonesia - Sri-Budayanti, N.; Sukrama, I. D. M.; Aditarini, M.; Sukardika, I. K.; Suata, I.K. (BALI MEDICAL JOURNAL, 2012)
Objective: Urinary tract infection (UTI) is the most common bacterial infection in general practice and in hospitals. Fast and accurate urine culture and sensitivity test are needed for adequate therapy. Anti Microbial Activity test (AMA test) that is used to detect the presence of antibiotics in urine specimens is not commonly used in clinical microbiology laboratories. Some laboratories are still using indirect inoculation technique using enriched media before inoculating onto the agar media. The aim of this research is to compare results of urinary examination of direct inoculation technique with AMA test with indirect inoculation technique without AMA test. Methods: A number of 210 urine specimens were collected in Clinical Microbiology Laboratory at Sanglah General Hospital within a time period between 16 June until 16 July 2009. Results: Antibiotics were detected in 40% of the urinary specimens; whereas 48.1% showed no evidence of UTI, that is negative AMA test and sterile urinary culture or colony growth < 105 CFU/ml. Only 11.9% of the specimens indicates urinary tract infections. The examination can be completed within 2-3 days which is shorter than indirect inoculation test which require 5-7 days. Direct inoculation technique can reduce the cost of production three-fold the costs require for an indirect inoculation test. Conclusions: Application of AMA test and direct inoculation technique can give results more rapidly, reliable and useful for clinicians. This also decrease the laboratory’s cost of production.